Measuring perceived exercise capability and investigating its relationship with childhood obesity: a feasibility study - Taylor,MJ; Arriscado,D; Vlaev,I; Taylor,D; Gately,P; Darzi,A (International Journal of Obesity, 2016)
Background/Objectives: According to the COM-B ('Capability', 'Opportunity', 'Motivation' and 'Behaviour') model of behaviour, three factors are essential for behaviour to occur: capability, opportunity and motivation. Obese children are less likely to feel capable of exercising. The implementation of a new methodological approach to investigate the relationship between perceived exercise capability (PEC) and childhood obesity was conducted, which involved creating a new instrument, and demonstrating how it can be used to measure obesity intervention outcomes.Subjects/Methods: A questionnaire aiming to measure perceived exercise capability, opportunity and motivation was systematically constructed using the COM-B model and administered to 71 obese children (aged 9–17 years (12.24±0.2.01), body mass index (BMI) standard deviation scores (SDS) 2.80±0.660) at a weight-management camp in northern England. Scale validity and reliability was assessed. Relationships between PEC, as measured by the questionnaire, and BMI SDS were investigated for the children at the weight-management camp, and for 45 Spanish schoolchildren (aged 9–13 years, (10.52±1.23), BMI SDS 0.80±0.99). A pilot study, demonstrating how the questionnaire can be used to measure the effectiveness of an intervention aiming to bring about improved PEC for weight-management camp attendees, was conducted. No participants withdrew from these studies.Results: The questionnaire domain (exercise capability, opportunity and motivation) composite scales were found to have adequate internal consistency (a=0.712–0.796) and construct validity (χ2/degrees of freedom=1.55, root mean square error of approximation=0.072, comparative fit index=0.92). Linear regression revealed that low PEC was associated with higher baseline BMI SDS for both UK (b=−0.289, P=0.010) and Spanish (b=−0.446, P=0.047) participants. Pilot study findings provide preliminary evidence for P